Sustainable Banking Disclosure and Bank Efficiency: Intellectual Capital as a Moderation Variable - Jati, Ahmad Waluya; Kholmi , Masiyah; Jannah, Wardatul (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this research is to examine how sustainable banking transparency affects bank efficiency and the moderating effect of intellectual capital. The research sample consists of banks that were listed on the Indonesia Stock Exchange in 2020–2022. Disclosure in sustainable banking is measured by content analysis. The bank efficiency value was obtained using the Data Envelopment Analysis (DEA) method. The research approach makes use of panel data regression. Ninety observations were gathered between 2020 and 2022 using the purposive sample approach. The study's conclusions show that information about sustainable banking has little bearing on bank efficiency. Intellectual capital can strengthen the link between bank efficiency and sustainable banking disclosure.